A Fully Adapted Headstage With Custom Electrode Arrays Designed for Electrophysiological Experiments - Mourão, Flávio Afonso Gonçalves; Guarnieri, Leonardo de Oliveira; Amaral Júnior, Paulo Aparecido; Carvalho, Vinícius Rezende; Mendes, Eduardo Mazoni Andrade Marçal; Moraes, Márcio Flávio Dutra (Frontiers in Neuroscience, 2022)
Electrophysiological recordings lead amongst the techniques that aim to investigate the dynamics of neural activity sampled from large neural ensembles. However, the financial costs associated with the state-of-the-art technology used to manufacture probes and multi-channel recording systems make these experiments virtually inaccessible to small laboratories, especially if located in developing countries. Here, we describe a new method for implanting several tungsten electrode arrays, widely distributed over the brain. Moreover, we designed a headstage system, using the Intan RHD2000 chipset, associated with a connector (replacing the expensive commercial Omnetics connector), that allows the usage of disposable and cheap cranial implants. Our results showed high-quality multichannel recording in freely moving animals (detecting local field, evoked responses and unit activities) and robust mechanical connections ensuring long-term continuous recordings. Our project represents an open source and inexpensive alternative to develop customized extracellular records from multiple brain regions.